2013
DOI: 10.1016/j.ecresq.2013.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Beyond an “Either–Or” approach to home- and center-based child care: Comparing children and families who combine care types with those who use just one

Abstract: Most research focuses on preschoolers’ primary non-parental child care arrangement despite evidence that multiple arrangements are relatively common. Using the nationally-representative Early Childhood Longitudinal Study, Birth Cohort, we compare characteristics and outcomes of families whose 4-year olds attend both home- and center-based child care with those who attend either home- or center-based care exclusively or receive no non-parental care at all. We find that about one fifth of 4-year olds attend both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 47 publications
2
28
0
1
Order By: Relevance
“…However, these proposed developmental benefits are potentially more prevalent for higher-income families, who may have a greater ability to intentionally arrange child care settings or provide children with stable, long-term concurrent arrangements (Pilarz & Hill, 2014), or for urban and suburban families, who may have a larger number of available child care options. For example, families may choose a range of concurrent child care options to capitalize on perceived benefits, such as positive social skills from a home-based setting and higher academic skills from a center-based setting (Bratsch, 2011; Gordon et al, 2013; Howes, 2010; Morrissey, 2009). …”
Section: Multiple Child Care Arrangementsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, these proposed developmental benefits are potentially more prevalent for higher-income families, who may have a greater ability to intentionally arrange child care settings or provide children with stable, long-term concurrent arrangements (Pilarz & Hill, 2014), or for urban and suburban families, who may have a larger number of available child care options. For example, families may choose a range of concurrent child care options to capitalize on perceived benefits, such as positive social skills from a home-based setting and higher academic skills from a center-based setting (Bratsch, 2011; Gordon et al, 2013; Howes, 2010; Morrissey, 2009). …”
Section: Multiple Child Care Arrangementsmentioning
confidence: 99%
“…Children may come in contact with a variety of peers who serve as source of direct or vicariously-acquired knowledge. Recent studies found that using particular combinations of multiple arrangements in the year prior to kindergarten, such as prekindergarten (pre-K) in combination with other center-based care, was positively associated with pre-K or kindergarten language and literacy outcomes (Forry et al, 2013; Gordon et al, 2013). Therefore, theoretically speaking, a more complex and supportive mesosystem could present greater developmental opportunities to the developing child.…”
Section: Multiple Child Care Arrangementsmentioning
confidence: 99%
See 3 more Smart Citations